2013
DOI: 10.1093/jxb/ert371
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and reactive oxygen species are involved in root aerenchyma formation and adaptation of wheat seedlings to oxygen-deficient conditions

Abstract: Ethylene-mediated reactive oxygen species signalling is involved in adaptive responses of wheat seedlings to waterlogged conditions through controlling formation of lysigenous aerenchyma and expression of genes encoding ethanol fermentation enzymes in roots

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
181
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(191 citation statements)
references
References 59 publications
7
181
1
2
Order By: Relevance
“…Constitutive aerenchyma is found in both wetland and nonwetland plants and can be further enhanced by flooding (Drew et al, 2000;Yamauchi et al, 2014). In other species, waterlogging induces aerenchyma formation (Rajhi et al, 2011;Yamauchi et al, 2014). Most research on aerenchyma formation has focused on lysigenous aerenchyma, which will be discussed here.…”
Section: Ethylene-mediated Flooding-adaptive Traitsmentioning
confidence: 99%
“…Constitutive aerenchyma is found in both wetland and nonwetland plants and can be further enhanced by flooding (Drew et al, 2000;Yamauchi et al, 2014). In other species, waterlogging induces aerenchyma formation (Rajhi et al, 2011;Yamauchi et al, 2014). Most research on aerenchyma formation has focused on lysigenous aerenchyma, which will be discussed here.…”
Section: Ethylene-mediated Flooding-adaptive Traitsmentioning
confidence: 99%
“…12 Non-ACC-pretreated wheat seedlings appeared to suffer severe damage under stagnant conditions before the emergence of adventitious roots, but adventitious roots that emerged in stagnant conditions were highly adapted to stagnant conditions as shown by their continued growth under stagnant conditions. 12 Together, these observations suggested that the adventitious roots emerged in stagnant conditions have some special features to adapt to oxygen-deficient conditions. In the present study, we assessed the effects of ethylene on the responses of adventitious roots to oxygen-deficient conditions.…”
mentioning
confidence: 98%
“…12 The seminal root tips of wheat seedlings grown under stagnant conditions died within 3 d. Although ACC-pretreated seminal roots of wheat seedlings grown under stagnant conditions avoided root tip death, they elongated very little. 12 Non-ACC-pretreated wheat seedlings appeared to suffer severe damage under stagnant conditions before the emergence of adventitious roots, but adventitious roots that emerged in stagnant conditions were highly adapted to stagnant conditions as shown by their continued growth under stagnant conditions. 12 Together, these observations suggested that the adventitious roots emerged in stagnant conditions have some special features to adapt to oxygen-deficient conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations